Hubungan Penyakit Periodontal pada Kehamilan dengan Kelahiran Bayi Prematur - Trijani Suwandi (Jurnal Kedokteran Gigi Terpadu, 2019)
Background: Periodontal disease could mediate the systemic effect through the action of periodontal pathogens and lipopolisacharide that  increase postaglandin and cytokine production, which will trigger the delivery of preterm low birth weight. Pregnant woman with periodontitis have significantly higher risk to deliver preterm low birth weight infants <37 weeks gestation period, and birth weight < 2500 gram. Periodontal therapy significantly reduces the rates of preterm low birth weight among women with periodontitis. Conclusions: It is concluded that periodontal disease as an independent risk factor for preterm low birth weight. Plaque control procedure during pregnancy should be considered to reduce the occurrence of preterm.